Monte Carlo Simulation of Adsorption of Pollutants Emitted from Uranium Chemical Processing Units Using Carbon Nanotube Membrane - Alireza Keshtkar; Mahmoud Rahmati (مجله علوم و فنون هسته‌ای, 2014)
The carbon nanotube membranes which have unique properties can make dramatic changes in adsorption and separation of compounds. Adsorption of pollutants from uranium chemical processing units is one of the most important environmental issues in this industry. Therefore, the adsorption isotherms of UO2, F2, UF6, UF4 and UO2F2 into carbon nanotube were studied by using the Monte Carlo simulation in order to evaluate the performance of carbon nanotubes membranes in the uptake of compounds of uranium chemical processing units. Also in this study, the effects of pressure and diameter of the carbon nanotubes on the adsorption of compounds were investigated. The results indicate that the adsorption of compounds onto the carbon nanotubes is as follows: UO2 > UF4 > UO2F2 > UF6 > F2. In other words, the maximum and minimum adsorption onto the carbon nanotubes are related to UO2 and F2, respectively. The effects of pressure and diameter of the carbon nanotubes on the adsorption of compounds show that the adsorption isotherm of all gases increases with increasing pressure and diameter of the nanotubes and the pressure influence on the adsorption of the compounds depends on the type of component and the carbon nanotubes diameter.